Development of Project-Based Learning-Based Learner Activity Sheet to Improve Creative Thinking Skills on Chemical Bonding - Syahidah, Nuril Auliyah; Rusmini, Rusmini (Jurnal Paedagogy, 2025)
This study aims to design and produce a Project-Based Learning (PjBL) oriented Learner Activity Sheet (LAS) to foster creative thinking abilities among learners in the context of chemical bonding. The study involved 31 students of class XI MIPA at SMAS Barunawati Surabaya. The study employed the 4D development model (Define, Design, Development, and Dissemination), but was limited to the Development stage. Several instruments were employed, including a media validation sheet, learner response questionnaire, observation data of learner activities and learning implementation, as well as tests for creative thinking skills and learning outcomes. The PjBL-based LAS for chemical bonding was evaluated for its feasibility and declared valid by three validators in terms of content and construct. It was also found to be practical based on positive student feedback and ’very good’ ratings for student activity and learning implementation. Furthermore, the tool proved effective, demonstrated by significant improvements in students’ creative thinking skills and cognitive learning outcomes. In conclusion, the developed Project-Based Learning LAS for chemical bonding fulfills the quality criteria of a teaching material in terms of validity, practicality, and effectiveness.